Pengaruh Zakat Infak Sedekah, Ekspor dan Konsumsi Rumah Tangga terhadap Pertumbuhan Ekonomi Indonesia Tahun 2015-2019 - Safitri, Wahyu; Pratama, Abdul Aziz Nugraha; Ratno, Fernaldi Anggadha (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
This research is motivated by the condition of economic growth which is always in a fluctuating state. So that variables that can strengthen or increase economic growth are needed. Economic growth is often associated with the welfare of a country's people. The purpose of this study is to determine the effect of Zakat Infak Sedekah (X1), Exports (X2) and Household Consumption to Indonesia's Economic Growth (Y) in 2015-2019. Samples were obtained as many as 60 data of BPS and BAZNAS. The data used in this study are sekunder data time series. Data analysis used statistical tests, Descriptive statistical test, stationarity test, multiple linear regression test and also classical assumption test (normality test, multicollinearity test, heterocesdasticity test, autocorrelation test and linearity test) with the help of Eviews version 11. The result of this study indicate that zakat infak sedekah has a positive and significant effect on economic growth, exports has a positive and significant effect on economic growth and household consumption has a positive and significant effect on economic growth.